Integrated Marketing Communication (IMC) and the role of Public Relations (PR) therein - Ilse Niemann-Struwig; Andrea Crystal; Anské Grobler (Communicare)
This study determines the role of public relations as a marketing communication function in University X’s integrated marketing communication approach. The research topic was selected for numerous reasons. Firstly, dramatic changes have occurred in the tertiary educational domain, which causes universities to adapt their marketing communication approaches. Based on these environmental changes, the Public Relations Division at University X commissioned the study on the research topic, which is the second consideration for the study. The debate on integrated marketing communication shows, in the third place, that this approach is increasingly important. On closer investigation there is a definite need for a thorough literature review with an authentic integrated marketing communication approach, driven by the integrated organizational functioning and processes. From a public relations perspective, on closer investigation, there is a need for the direct empirical examination of the role of public relations as a contributing function of integrated marketing communication in order to narrow the gap between literature and empirical evidence. The study was enhanced by two phases of research conducted within University X to meet the objectives of the study. The first, quantitative phase determined the extent to which University X’s communication activities are integrated. The measuring instrument used is the integrated marketing communication mini-audit scale. In the second, qualitative research phase, the role of public relations as a marketing communication function within University X’s integrated marketing communication approach was determined. The issue that became apparent throughout this study was that integrated marketing communication in any organizational context is of strategic importance for the “unity of effort” of the greater well-being of the organization. It was found in this research project that there are fundamental concerns for University X regarding integrated marketing communication, and that public relations is practised on a technical, traditional level